Manajemen Integrasi Kurikulum Pesantren dan Kurikulum 2013 Pada Kegiatan Ekstrakurikuler di SMA Sabilut Thoyyib Kota Pasuruan - Fisona Fisona; Imam Syafi’i; Ashari Ashari (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research uses qualitative research with a case study approach. Data collection was carried out by interviews, observation and documentation. The data analysis process is carried out starting from data collection and checking the validity of the data. To check the validity of the research data using the data triangulation method.The research results show that: 1) Planning by: a) integrating curriculum objectives, namely using the same vision and mission, b) integrating the organization of curriculum content by pairing Islamic boarding school material and school material in general knowledge, this curriculum organization is included in the form of integration in the form of extracurricular activities;. 2) Implementation by: by: a) integrating curriculum implementation programs, namely academic calendars and joint school and Islamic boarding school academic activity plans, academic activities such as daily schedules for students, matsada, wama, high school and family convergence, student achievements, graduation certificates, b) integrating supervision of curriculum implementation with cooperation between Islamic boarding schools and schools; 3) Evaluation by: a) evaluating the context of the joint curriculum, which includes: socio-cultural development, development of science and technology, b) evaluating joint input, which includes: competency of teaching staff, readiness of students and availability of learning media/facilities, c ) conducting joint process evaluations, including: weekly evaluations and incidental evaluations, and d) conducting joint product evaluations, which include: mid-year evaluations and end-of-year evaluations. Keywords: Management of Islamic Boarding School Curriculum Integration, Extracurricular Activities